Recurrent post-tonsillectomy bleeding due to an iatrogenic facial artery pseudoaneurysm - Choi, Kevin J. (Acta Otolaryngol Case Rep, 2017)
This is a report of an illustrative case of recurrent post-tonsillectomy bleeding that was caused by an iatrogenic facial artery pseudoaneurysm and controlled by endovascular embolization. A 37 year-old female who underwent bilateral tonsillectomy for chronic tonsillitis had recurrent secondary hemorrhage despite multiple operative interventions to control the bleeding. Because of the recurrent nature of the bleeding, an angiography of the external carotid artery was performed demonstrating a pseudoaneurysm of the left facial artery with active extravasation. This was successfully embolized with ethylene vinyl alcohol copolymer and the bleeding did not recur. Most post-operative bleeds can be managed with bedside or intraoperative interventions. However, pseudoaneurysms should be considered in the differential diagnosis of recurrent bleeds refractory to surgical control.